THE ANALYSIS OF SPEAKING MATERIALS IN “SCAFFOLDING” ENGLISH TEXTBOOK FOR THE NINTH GRADERS AND THEIR RELEVANCE TO SI 2006 (RETAIN, 2013)
Among the 4 skills, speaking is the most vital skill in English; this is so because the ability to function in another language is generally characterized in terms of being able to speak that language (Nunan, 1991:225). To teach speaking, the teachers need appropriate materials. There are many learning resources that can be used as teaching materials. One of the materials is a textbook. Textbook is designed based on the curriculum in its country and reflected assumptions of teaching practices of how foreign languages are learned. Based on the explanation, the SCAFFOLDING English textbook for The Ninth Graders was analyzed to decide whether the speaking materials in the textbook fulfilled the criteria of good speaking materials and based on Standar Isi 2006 (SI) in order to find the relevance between these two references. The design of this study is descriptive qualitative and the subject of this study is the English textbook SCAFFOLDING. The results of this study shows that the speaking materials in this book are included into good speaking materials because it has fulfilled two of three criteria of good speaking materials and the speaking materials in Scaffolding English textbook are relevant to speaking materials stated in Standar Isi 2006. Furthermore, the speaking materials of this textbook need to be revised so that, the objective of language teaching, especially speaking can be reached. Keywords: Relevance, Speaking materials, Textbook, Standar Isi 2006 (SI).